2021
DOI: 10.1093/pm/pnab123
|View full text |Cite
|
Sign up to set email alerts
|

The Great Trade-off in Workers’ Compensation: Perceptions of Injustice by Those Experiencing Persistent Pain

Abstract: Introduction Some claimants harbor perceptions of injustice about the way they have been treated. In particular, those with ongoing and disabling pain have been generally dissatisfied by the way they have been managed by the systems designed to offer them financial compensation. Aim To explore possible factors that may contribute to their dissatisfaction. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This suggestion resonates with a recent paper describing the historical origins of excluding pain from compensation, and concluding that the resulting WC systems fail to address certain harms and may contribute to perceptions of injustice and adverse health outcomes. 45 The findings of this study suggest that, although the majority of workers appraised WC-based RTW programs favorably, there is also substantial room for improvement in workers' experience with the WC system. In addition, injured workers' feedback may reflect opportunities to reduce administrative burden and to improve health and RTW outcomes.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This suggestion resonates with a recent paper describing the historical origins of excluding pain from compensation, and concluding that the resulting WC systems fail to address certain harms and may contribute to perceptions of injustice and adverse health outcomes. 45 The findings of this study suggest that, although the majority of workers appraised WC-based RTW programs favorably, there is also substantial room for improvement in workers' experience with the WC system. In addition, injured workers' feedback may reflect opportunities to reduce administrative burden and to improve health and RTW outcomes.…”
Section: Discussionmentioning
confidence: 70%
“…The Washington State Department of Labor and Industries (L&I) administers the WC system, which includes the State Fund (covering about 70% of workers specified by Washington's Industrial Insurance Act 45 ), and self-insured employers (covering the remaining 30%).…”
Section: Study Population and Data Sourcesmentioning
confidence: 99%
“…Still, loss of (future) income and general compensatory damages will be relevant issues to patients in both settings. Additionally, feelings of psychological distress [ 7 ] and perceived injustice [ 23 , 28 ] will affect personal injury claim patients irrespective of country, suggesting that the similarities in personal injury claims between countries may outweigh the differences. This is in line with a meta-analysis of surgical treatment outcomes of patients with workers compensation or involved in litigation [ 15 ], where it was shown that the association between compensation and worse treatment outcomes was consistently present in the United States, Canada, Europe, and Australia.…”
Section: Discussionmentioning
confidence: 99%